Development of a Scientific Mind Test for Prathomsuksa 6 Students under Samutsongkharm Primary Educational Service Area - Permsopa, Wannaporn; Chairattanawan, Kanidta; Lapanachokdee, Warunee (Arts of Management Journal, 2020)
The purpose of this research was to develop the Scientific Mind Test for Prathomsuksa 6 students under Samutsongkharm Primary Educational Service Area. The four specific objectives were as follows: 1) to develop the Scientific Mind Test; 2) to validate the Scientific Mind Test; 3) to establish norms of the Scientific Mind Test; and 4) to construct the manual of the Scientific Mind Test. The instrument used was stratified random sampling method, research sample for scale validation and norms construction consisted of 305 Prathomsuksa 6 Students who studied in schools in Samutsongkharm Primary Educational Service Area in second semester, academic year 2020. The developed Scientific Mind Test comprised of 30 items, aimed to assess 10 Scientific mind comprised of 10 features; Curiosity, Rationality, Open-mindedness, Honesty, Determination, Prudence, Responsibility, Cooperation, Creatively and Positive Attitude toward science. The Scientific Mind Test is situation test with five different score choices. The research results showed that the developed Scientific Mind Test could be efficiently used to assess the Scientific Mind Test of prathomsuksa 6 students under Samutsongkharm Primary Educational Service Area. The significant findings were as follows: 1) The content validity of the Scientific Mind Test, investigated by calculating the item objective congruence Index (IOC), was in the range of 0.60-1.00; 2) The item discrimination index was in the range of 0.31-0.68; 3) The construct validity of Scientific Mind Test, investigated by confirmatory factor analysis, revealed that construct validity of the Scientific Mind Test was achieved, Chi-Square (X2) with 323 df was 302.76 (p=0.78); RMR was 0.047 ; RMSEA was 0.00 ; GFI was 0.94; and AGFI was 0.91; 4) Cronbach’s alpha reliability coefficient of each featured were 0.70, 0.73, 0.72, 0.70, 0.71, 0.71, 0.70, 0.74, 0.77 and 0.81, respectively; 5) The norms for the Scientific Mind Test’s score interpretation presented in the form of the normalized T-score were in the range of T16– T82; and 6) The manual of the Scientific Mind Test was suitable and convenient for usability, explain to direction obviously and fully important composition.